2020
DOI: 10.1101/2020.03.22.20040832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with prolonged viral shedding and impact of Lopinavir/Ritonavir treatment in patients with SARS-CoV-2 infection

Abstract: Background: The duration of viral shedding is central to guide decisions around isolation precautions and antiviral treatment. However, studies about risk factors associated with prolonged SARS-CoV-2 shedding and the potential impact of Lopinavir/Ritonavir (LPV/r) treatment remain scarce. Methods: In this retrospective study, data were collected from all SARS-CoV-2 infected patients who were admitted to isolation wards and had RT-PCR conversion at the NO.3 People's hospital of Hubei province between 31 January… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 18 publications
0
32
0
7
Order By: Relevance
“…One retrospective study [54] included 78 patients with COVID-19 infection with lopinavir-ritonavir and 42 without lopinavir-ritonavir (non-critical patients). The median time of positive-to-negative conversion of RT-PCR test in the lopinavir-ritonavir group was shorter than the control group (22 (IQR, 18-29) days vs. 28.5 (IQR, 19.5-38) days, P = 0.02) within 10 days, and did not show a significant difference > 10 days (median27.5 days vs. 28.5 days, P = 0.86).…”
Section: Implementation Considerationmentioning
confidence: 99%
“…One retrospective study [54] included 78 patients with COVID-19 infection with lopinavir-ritonavir and 42 without lopinavir-ritonavir (non-critical patients). The median time of positive-to-negative conversion of RT-PCR test in the lopinavir-ritonavir group was shorter than the control group (22 (IQR, 18-29) days vs. 28.5 (IQR, 19.5-38) days, P = 0.02) within 10 days, and did not show a significant difference > 10 days (median27.5 days vs. 28.5 days, P = 0.86).…”
Section: Implementation Considerationmentioning
confidence: 99%
“…Five patients in the lopinavir-ritonavir group experienced adverse events (gastrointestinal and deranged liver function), whilst no adverse events occurred in the Umifenovir or control groups. Another clinical trial of 120 patients in China, (20) 78 patients (65%) recieved lopinavir-ritonavir treatment and were categorized as severe COVID-19 . they had a higher ratio of lymphocyte count <0.8×109/liter than those without lopinavir-ritonavir treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In another retrospective study of 323 patients in Wuhan, LPN/r was more given to critical patients (46.2%) than non-critical cases (5.4%) and more administered in unfavorable than favorable outcomes (23.8% vs. 5.0%) [56]. Furthermore, treatment with LPN/r was reported to be independently associated with the prolongation of virial RNA shedding (OR = 2.42, 95% CI = 1.10 -5.36) and earlier provided LPN/r might shorten the viral shedding as well (22 days vs. 28.5 days, P = 0.02) [68]. Findings from the efficacy of lopinavir plus ritonavir and arbidol against novel coronavirus infection (ELACOI) trial also suggested the little benefit improvement of LPV/r in clinical outcomes among non-severe patients, compared with supportive care [57].…”
Section: Lopinavir/ritonavirmentioning
confidence: 99%